Motion in Games 5th International Conference, MIG 2012, Rennes, France, November 15-17, 2012. Proceedings - Kallmann, Marcelo; Bekris, Kostas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 5th International Workshop on Motion in Games, held in Rennes, France, in November 2012. The 23 revised full papers presented together with 9 posters and 5 extended abstracts were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on planning, interaction, physics, perception, behavior, virtual humans, locomotion, and motion capture.
Moving Path Planning Forward -- Environmental Effect on Egress Simulation -- Following a Group of Targets in Large Environments -- Realtime Performance Animation Using Sparse 3D Motion Sensors -- A Game System for Speech Rehabilitation -- Virtual Try-On Using Kinect and HD Camera -- Physics -- Modal Vibrations for Character Animation -- Modeling Physically Simulated Characters with Motion Networks -- A Unified Constraint Framework for Physical Animation of Articulated Rigid Bodies -- Appealing Virtual Humans -- Perception of Complex Emotional Body Language of a Virtual Character -- Conveying Real-Time Ambivalent Feelings through Asymmetric Facial Expressions -- Automating the Transfer of a Generic Set of Behaviors onto a Virtual Character -- A Crowd Modeling Framework for Socially Plausible Animation Behaviors -- Controlling Three Agents in a Quarrel: Lessons Learnt -- Virtual Humans -- What$1 (Bs Next? The New Era of Autonomous Virtual Humans -- Virtual Humans: Evolving with Common Sense -- Locomotion -- Principles and Observation: How Do People Move? -- Using Optimal Control Methods to Generate Human Walking Motions -- Interactive Quadruped Animation -- Capturing Close Interactions with Objects Using a Magnetic Motion Capture System and a RGBD Sensor -- An Analysis of Motion Blending Techniques -- Automatic Hand-Over Animation for Free-Hand Motions from Low Resolution Input -- A Perceptual Study of the Relationship between Posture and Gesture for Virtual Characters -- Walker Speed Adaptation in Gait Synthesis -- An Efficient Energy Transfer Inverse Kinematics Solution -- Motion Planning with Discrete Abstractions and Physics-Based Game Engines -- Calibrating a Motion Model Based on Reinforcement Learning for Pedestrian Simulation -- A*mbush Family: A* Variations for Ambush Behavior and Path Diversity Generation -- Fuzzy Logic Controlled Pedestrian Groups in Urban Environments -- Enhancing the Behavior of Virtual Characters with Long Term Planning, Failure Anticipation and Opportunism -- Realtime, Physics-Based Marker Following -- Fast Motion Retrieval with the Distance Input Space -- Machine Learning Approach for Gesture Recognition Based on Automatic Feature Selection -- Dealing with Variability When Recognizing User$1 (Bs Performance in Natural Gesture Interfaces -- Treating Phobias with Computer Games -- Analysis and Verification of Navigation Strategies by Abstract Interpretation of Cellular Automata.s
Keywords: Computer science; Artificial intelligence; Computer simulation; Computer vision; Computer graphics; Computer Science; Computer Imaging, Vision, Pattern Recognition and Graphics; Artificial Intelligence (incl. Robotics).; Simulation and Modeling; User Interfaces and Human Computer Interaction; Computer Graphics; Image Processing and Computer Vision